KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH - Herlina Herlina; Oqi Rizqiandi (Universitas La Tansa Mashiro, 2017)
This study aims to determine the effect of hotel tax on the local original revenue in Lebak Regency Period 2012-2016. The independent variable in this study is Hotel Tax. Dependent variable is Local Original Revenue (PAD).The method used in this research is quantitative method with simple linear analysis, the sample is taken for five years using secondary data from Local Revenue Board (BAPENDA) that is in the form of Realization Report of Lebak District Budget and Local Realization Report of 2012-2016 period. The statistic test used is classical assumption test, simple regression analysis, product moment correlation analysis, coefficient of determination, hypothesis test and using the help of SPSS V20 application program.Based on the analysis contribution, the contribution of hotel tax to Local Revenue per year consecutive from 2014 to 2016 is 0.092%, 0.089%, 0.093%. Based on the coefficient of determination obtained R Square 0,970 so that obtained coefficient of determination 0,456 x 100% = 45,6%, the result means that hotel tax variable can influence variable of local original revenue equal to 45,6%. And based on the t test shows that hotel tax has a significant positive effect on Local Original Revenue (PAD) with significance value smaller than 0.05 that is equal to 0.000.